2015
DOI: 10.1097/aap.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Changes in Ropivacaine Concentration and Analgesic Effects Between Transversus Abdominis Plane Block and Rectus Sheath Block

Abstract: Peak ropivacaine concentrations were comparable during TAPB and RSB, but peaked earlier during TAPB. Although 150 mg of ropivacaine remained effective significantly longer during TAPB than RSB during laparoscopic surgery, this dose could cause local anesthetic systemic toxicity. The analgesic effects of blocks with less ropivacaine should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…Previous studies on the rise in plasma ropivacaine concentration reported that Tmax was 23.1 min and 48.5 min after TAP block and rectus sheath block , respectively. Similarly, another study reported that Tmax of ropivacaine was 35 min and 53 min after TAP and rectus sheath block, respectively. These reports showed that the Tmax after rectus sheath block took approximately twice as long as the Tmax after TAP block, which is similar to the results we observed with levobupivacaine.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies on the rise in plasma ropivacaine concentration reported that Tmax was 23.1 min and 48.5 min after TAP block and rectus sheath block , respectively. Similarly, another study reported that Tmax of ropivacaine was 35 min and 53 min after TAP and rectus sheath block, respectively. These reports showed that the Tmax after rectus sheath block took approximately twice as long as the Tmax after TAP block, which is similar to the results we observed with levobupivacaine.…”
Section: Discussionmentioning
confidence: 78%
“…The effects of abdominal truncal blocks, such as TAPBs and rectus sheath block, are relatively short. 3,7 The exception is PVB, the analgesic effect of which can last for 24 hours with long-acting local anesthetics. 8 Although QLB was reportedly effective against abdominal somatic pain, 9 the duration of the block had been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although pain scores and overall opioid consumption may be reduced in some settings for up to 24 to 48 hours, 77,91 when block duration is measured by offset of sensory block or time to first request for rescue analgesia, volunteer and clinical studies of both landmark-guided 77,90,91 and US-guided approaches 13,28,121,122 indicate that this ranges from 6 to 10 hours on average with bupivacaine or ropivacaine. Although this can be overcome by placement of catheters in the TAP plane, either percutaneously or surgically, there are several issues to be considered.…”
Section: Single-shot Versus Continuous Tap Blockmentioning
confidence: 99%
“…Patients should also be closely monitored for at least 30 to 45 minutes because this is the average time to peak plasma concentration following truncal blocks. 22,49,122,132,136,173,272 …”
Section: Local Anesthetic Systemic Toxicitymentioning
confidence: 99%